Strategi Komunikasi Pelayanan Publik Terpadu Satu Pintu Kota Bengkulu - Eceh Trisna Ayuh; Susi Nurfitriani (JOPPAS: Journal of Public Policy and Administration Silampari, 2019)
The purpose of this study was to determine the organizational communication strategy used by the Office of Investment and Integrated Licensing Services at the One Door of Bengkulu City in an effort to improve public services, as well as to identify the obstacles that arise when implementing organizational communication strategies. The theory used in this study is the theory put forward by Karl Weick in 1969 in which organizations were not formed from structures and positions but from communication activities. This research uses a descriptive qualitative approach. Informants from the study consisted of 10 employees of the Office of Investment and Integrated Licensing Services of One Door Bengkulu City Government who were selected based on purposive sampling technique. Data collection techniques used in this study were interviews and observation. The results showed that the strategy used was building internal communication among members of the organization, building emotional closeness and increasing awareness of members of the organization, evaluating the performance that has been done, always being tolerant of the fellow members of the organization. Barriers that arise during communication are differences in the character of each person, frequent mutations and employee movements, lack of competent ability of some employees. Conclusion, if communication between organizations is effective, then all systems can run well, including in terms of public services. Keywords : Communication Strategies, Public Services, DPMPTSP